Strategies for Preventing or Reduction of Cognition, Motivation and Emotional Biases in Accounting - Jaworska , Elżbieta (Studia Oeconomica Posnaniensia, 2018)
The purpose of the article is to highlight the importance of counteracting errors and distortions in the cognitive process. This article reviews behavioral factors influencing professional accountants' behavior and the resulting cognitive, motivational and emotional errors. The prevention or elimination strategies proposed in the social sciences have been explored, and various techniques have been analysed to counter or reduce errors from the accounting perspective. This article is based on literature studies. The method of analysis of the sources and synthesis, induction and inference were used.